Optimization of Medicinal Treatment of Patients with Glaucoma in Combination with Concurrent System Pathology. Part 1: Cardiovascular Pathology - A. N. Zhuravleva; M. V. Zueva; E. B. Shustov (Oftalʹmologiâ)
This paper presents clinical and pharmacological drug interactions for the treatment of patients with glaucoma combined with concurrent cardiovascular pathology, risks of side effects, and adverse drug reactions. The article discusses the multifactor nature of glaucoma, age factors, and the direction of local and systemic pathogenetic treatment, principles of the personified approach, and its feasibility. It is shown that an essential element of this approach can be a system of questionnaires for glaucoma patients with chronic diseases, the principal place in which is occupied by a questionnaire filled out by the patient himself. Digital processing of individual data and assessments provided by patients allows us to implement the tasks of a personalized approach to the treatment. Analysis of the pharmacological effects of the available and used arsenal of medicinal products allows you to generalize the array of data obtained, to form model algorithms for deciding by an ophthalmologist on the choice of medications. In scheme optimizing of the prescribed medications, it is important to cross-inform between specialists of different profiles (ophthalmologists, therapists, neurologists, cardiologists, endocrinologists, rheumatologists, etc.), create an algorithm for entering the medications of choice and their rational combinations, which reduces the risk of polypragmasia. Possible causes of progression of glaucoma optic neuropathy (GON) against the background of age-related systemic diseases (using the example of the cardiovascular system’s pathology) are considered. Ways of influencing the pathogenetic links of the glaucomatous process are proposed from the standpoint of an optimal combination of medications. Analysis of literature on the problem of structural and functional disorders in GON’s development shows that it is promising to expand our understanding of the fundamental processes underlying these changes, search for clinically significant combinations of contemporary markers of changes in structure and function, and, accordingly, treatment approaches. The possibilities of neuroprotection of glaucoma optical neuropathy, as well as modern methods of electrophysiological research in the monitoring assessment of its effectiveness and the differential diagnosis, approaches to enhance the effectiveness of medications treatment with combined medications are analyzed in the article.